STUDI KEKERABATAN IKAN FAMILIA CYPRINIDAE YANG TERTANGKAP DI SUNGAI SERAYU KABUPATEN BANYUMAS - Dwi Sekar Putri J; Muh. Nadjmi Abulias; Dian Bhagawati (Scripta Biologica, 2014)
Cyprinidae is a family of freshwater fish that has quite a lot of valuable members and spread almost all over the world. The purpose of this study was to determine the number of fish of the family Cyprinidae in Serayu River and their relationships. This study used survey method with purposive random sampling. Research materials were members of Cyprinidae taken from the River Serayu Banyumas, which was the collection of Mrs. Dian Bhagawati. The sequence of this study included sample collection, sample preservation, sample observation in the laboratory, i.e., identification, determination of morphological characters and species name of fish and their relationships. Observed variables were morphological characters that included body shape, colors, fins specification, the total and standard length of the body, the shape of the lateral line, the shape of the caudal fin, the position of the mouth, body length, the height and width of the caudal peduncle. The data were then computed to get the coefficient of association among species (S), clustered using UPGMA Cluster Analysis as implemented in Numerical Taxonomy System (NTSYS) version 2.02i. The observed data were also descriptively analyzed based on phenogram obtained. The fish diversity recorded were eight species i.e., Puntius orphoides, Barbodes gonionotus, Osteochilus sp., Osteochilus vittatus, Osteochilus hasselti., Labiobarbus leptocheilus, Cyprinus carpio, and Rasbora sp.. The results showed that the closest relationship based on morphological characteristics was between Puntius orphoides and Rasbora sp. which had the greatest association coefficient of 0.8292. The smallest value of the association was followed by P. orphoides and Osteochilus sp. with the value of 0.3000. This study was expected to provide information of Cyprinid fish in Serayu River and their phenetic relationship.